The Influence of Role Clarity, Work Environment, and Job Satisfaction on Career Commitment (An Empirical Study at the Regional Secretariat and DPRD Secretariat of Tanah Datar Regency) - Hidayat, Rahmat; Yunus, Mukhlis (Equator Journal of Management and Entrepreneurship (EJME), 2025)
This study aims to examine and validate the influence of role clarity, work environment, and job satisfaction on career commitment. The population in this research consists of 100 employees at the Regional Secretariat and DPRD Secretariat of Tanah Datar Regency, with 100 respondents successfully processed. The data used is primary data, collected through questionnaires. The analytical tool employed in this study is SmartPLS 3.3.3 software. The results indicate that role clarity has a positive influence on career commitment, and job satisfaction also positively impacts career commitment at the Regional Secretariat and DPRD Secretariat of Tanah Datar Regency. However, the work environment does not affect career commitment in this context.